Preventing Security Risks in Government Information Disclosure: A Mosaic Theory Perspective - Chen, Ling (Journal of Global Economy, Business and Finance, 2024)
The security risks in government information disclosure are directly related to the effective operation of the information society and have significant theoretical and practical value for information security governance and the improvement of the national security strategy system. This article uses mosaic theory's "information synergy effect" and life cycle theory to examine the stages of information collection, embedding, and utilization, focusing on key aspects such as risk source formation, risk transmission, and social amplification of risks. It analyzes the security risks and related typical events in government information disclosure and proposes prevention measures. The results show that security risks generally follow the logic of "internal and external factors trigger—direct information damage—secondary information loss of control—imbalance of information ecology." Therefore, the full-process governance of security risks in government information disclosure is a continuous project that involves building security barriers and adjusting the scope of disclosure in the information collection phase before the risk source is formally generated to prevent the formation of risk sources. In the information embedding phase, illegal processing should be prevented, emergency plans established, and all-around and multiangle prevention warnings and overall treatment carried out to ensure national security